E-167 Mechanical thrombectomy for ischemic stroke secondary to large vessel occlusions in patients on extracorporeal membrane oxygenation. (23rd July 2022) - Kohli, G; George, D; Grenga, A; Bjelic, M; Gosev, I; Schartz, D; Kessler, A; Khan, I; Bhalla, T; Mattingly, T; Bender, M
Abstract : Introduction: The use of mechanical circulatory support (MCS) such as left ventricular assist devices (LVADs) and extra corporeal membrane oxygenation (ECMO) is becoming a routine practice at many centers. The aim of this case series and review is to document our experience with mechanical thrombectomy (MT) for MCS-related ischemic stroke and to explore the complicated management and treatment considerations of stroke in the context of these circulatory support devices. Methods: We retrospectively reviewed all patients ECMO who underwent MT for large vessel occlusion (LVO) since 2017 at our institution. Baseline demographics, details regarding placement of ECMO and outcome variables such as recanalization scale, any hemorrhage on post-operative imaging, and mRS at three months were collected for each patient. Results: There were three patients on ECMO identified to have a LVO between 2020–2021. Two patients had internal carotid terminus occlusions and one had a basilar occlusion. The average time from last known well to groin puncture was 294 minutes and the average time to recanalization from groin access was 58 minutes. Two ECMO patients required radial access due to either central aortic cannula or presence of intra-aortic balloon pump. All three patients had TICI 3 revascularization without hemorrhage on post-operative imaging. All patients were eventually decannulated from ECMO. Two patients had mRS 1 at 3 months while one patient was mRS 4. Conclusion: Concomitant with the increasing use of ECMO is the increasing recognition of acute brain injuries, including acute ischemic stroke, which may be caused by a myriad of MCS-driven factors. We share our institutional experience with performing MT in patients on circulatory support and demonstrate that mechanical thrombectomy can be performed safely with good outcomes. Disclosures: G. Kohli: None. D. George: None. A. Grenga: None. M. Bjelic: None. I. Gosev: None. D. Schartz: None. A. Kessler: None. I. Khan: None. T. Bhalla: None. T. Mattingly: None. M. Bender: None.